MANAJEMEN RISIKO GADAI EMAS PADA PT.PEGADAIAN SYARIAH JAYAPURA : (Studi Kasus PT. Pegadaian Syariah Unit Pelayanan Syariah Heram) - Yunita Sari; Syaiful Muhyidin; Fachrudin Fiqri Affandy (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2020)
The background of this research is the high level of public interest in product of sharia gold pawn so that the risk management is the main focus to be carried out. The most common risk is the risk of loans, especially gold pawn loans. The risk of goal pawn loans becomes the main focus on the Islamic Pawnshop. This is based on the limitations of employees of PT. Pegadaian Syariah Jayapura, especially UPS Heram, in screening data for funding applications. These limitations lead to several stages of loans that are not intentionally or deliberately by passed to accelerate the loans process. This research used qualitative approach with the case study method. It used primary and supporting data. The information from primary data sources in qualitative research can generally be explored through observation and interview techniques. This research shows that PT. Jayapura Syariah Pegadaian (UPS) Heram in managing gold pawning risk can be from the risk management process, namely risk identification, risk measurement, and risk management. The mitigation of gold pawn transactions include the risk mitigation of the accuracy of the gold assessment, the risk mitigation of a decline in the price of gold, the risk mitigation of storing gold. The minimizing of the risks that might occur use monitoring, guidance and supervision of internal risks.